Presence of Circulating Tumor Cells Predates Imaging Detection of Relapse in Patients with Stage III Melanoma - Lucci, Anthony; Addanki, Sridevi; Chiang, Yi-Ju; Meas, Salyna; Sarli, Vanessa N.; Upshaw, Joshua R.; Manchem, Mayank; Patel, Sapna P.; Wargo, Jennifer A.; Gershenwald, Jeffrey E.; Ross, Merrick I. (Cancers, 2023)
Stage III melanoma includes nodal metastasis or in-transit disease. Five-year survival rates vary between 32% and 93%. The identification of high-risk patients is important for clinical decision making. We demonstrated previously that ≥1 circulating tumor cells (CTCs) at baseline was associated with recurrence. In this study, we investigated how frequently CTCs were identified prior to radiologically detected recurrence. Stage III patients (n = 325) had imaging at baseline and q 3 months. Baseline and q 6–12 months blood draws (7.5 mL) were performed to identify CTCs up to 3.5 years from diagnosis. CTC assessment was performed using the immunomagnetic capture of CD146-positive cells and anti-MEL-PE. The presence of one or more CTCs was considered positive. We analyzed the cohort of patients with relapse confirmed by radiologic imaging. CTC collection dates were assessed to determine the lead time for CTC detection. CTC-negative patients were significantly less likely to relapse compared to patients positive for CTCs (p-value < 0.001). Within the 325-patient cohort, 143 patients (44%) had recurrence, with a median follow-up of 52 months from diagnosis. The cohort (n = 143) with positive imaging and CTC results revealed 76% of patients (108/143) had CTC+ results before the radiological identification of relapse. The median time between positive CTC and positive imaging was 9 months. CTCs were positive in >75% of patients prior to relapse at a median of 9 months before radiologic detection.